Pengaruh Media Sosial dan Game Online Terhadap Pelaksanaan Ibadah Siswa (Studi Kasus SMK Citra Bangsa Kecamatan Kemang Kabupaten Bogor) - Fauzi, Ikbar; Dimyati Bz, Ahmad; Al Ghifary, Muh. Ubaidillah (Jurnal Paedagogy, 2022)
The purpose of this study was to analyze the effect of using social media and online games on the implementation of worship on students at SMK Citra Bangsa, Kemang District, Bogor Regency. This study uses a quantitative approach with the correlation method. The sample of this study amounted to 235 students. This research instrument in the form of a questionnaire and documentation. The data analysis technique uses product moment correlation analysis. The results showed that 1). a description of the use of social media in students at SMK Citra Bangsa the percentage is 98% and those who do not use it are 2%. While the use of online games from 235 respondents; those who use it are 122 respondents with a percentage of 52%, and those who do not use it are 113 respondents with a percentage of 48%, 2). the description of the implementation of student worship in the school is a. obligatory prayers: those who perform 89%, those who do not 11%, b. sunnah prayer; implementing 46%, not implementing 54%, and c. sunnah fasting; those who practice 4% and those who do not practice 96%, and 3) the effect of the use of social media and online games on the implementation of student worship at the school is not significant with 4.8%, namely the percentage from 100% -4.8 = 95.2% influenced by other factors, this is obtained from the price of R2 = 0.048.